2023
DOI: 10.1155/2023/6177201
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Performance Piezoelectric Energy Harvester Using Lead-Free Piezoceramics with Large Electromechanical Coupling Factor

Abstract: The output power of piezoelectric energy harvester (PEH) at the resonance frequency is dependent on the electromechanical coupling factor ( k p ) of the piezoceramic, which is proportional to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…S6(f), ESI†) with a P S direction along the [001] direction. 29,39,60 Previous studies reported identical results. 29,39,60…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…S6(f), ESI†) with a P S direction along the [001] direction. 29,39,60 Previous studies reported identical results. 29,39,60…”
Section: Resultsmentioning
confidence: 67%
“…It has been reported that the P out of type-I harvesters at f R is affected by the k p 2 of the composition. 10,39 Fig. 10(d) shows the P out of the harvesters and the k p 2 value of the textured NK(N 1− x S x )–CZ–BAZ 0.0 ≤ x ≤ 0.1 compositions, which shows that the change in the P out value was identical to that of the k p 2 value.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations